Polarization multiplexing for double images display - Guo Jinying (Institue of Optics and Electronics, Chinese Academy of Sciences, 2019)
Metasurface provides subwavelength structures for manipulating wavefronts of light. The benefits of subwavelength components offer a continuous modulation of amplitude, phase, and polarization, thus eliminating the production of higher-order images and improving the utilization of light intensity. Despite the rapid progress in this field, multiparameter control of light using single layer metasurface is rarely reported. In fact, multiparameter control of light helps to improve information storage capacity and image fidelity. With simultaneous manipulation of polarization and amplitude at each pixel, it is possible to encode two separate images into one metasurface and reconstruct them under proper conditions. In a proof of concept experiment, we demonstrate an independent display of two binary images at the same position with polarization de-multiplexing from a single metasurface. This unique technology of encoding two images through amplitude and polarization manipulation provides a new opportunity for various applications in, such as encryption, information storage, polarization holograms, optical communications and fundamental physics.